KONTRIBUSI KOMUNIKASI ANTARPRIBADI DAN KONSEP DIRI TERHADAP KINERJA GURU PESANTREN TERPADU SERAMBI MEKKAH KOTA PADANGPANJANG - Albert Albert (al-fikrah: Jurnal Manajemen Pendidikan, 2018)
This study aims to examine the contribution of Inter-Personal Communication and Self- Concept to Teachers' Performance of Integrated Boarding School of Serambi Mekkah  of Padang Panjang. The studied variables are Interpersonal Communication and Self Concept as the  independent variables and Teachers'  Performance  as  the dependent variable. The respondents  of the  research are  54 teachers of Integrated Boarding School of Serambi Mekkah  of Padang Panjang. The specified sample is 48 people. Sampling is done by using Proportional Sampling technique. Data were collected by questionnaire, then analyzed by using Correlation Analysis and Regression technique to find out its contribution by using partial analysis. The results of the  data analysis revealed that: 1) Interpersonal Communication significantly influences the performance of teachers, 2) Self-Concept significantly influences the performance of teachers, and 3) interpersonal communication and self-concept simultaneously , and significantly influences the performance of teachers. From the above findings,  it can be concluded that the teachers' interpersonal communication and self-concept are  two important factors that can affect the performance of the  teacher, despite other factors contribution. Finally, it is  recommended to all parties in Integrated Boarding School of Serambi Mekkah  of Padang Panjang to give serious attention to both factors above.